2010
DOI: 10.1158/1078-0432.ccr-10-0385
|View full text |Cite
|
Sign up to set email alerts
|

AdCD40L Immunogene Therapy for Bladder Carcinoma—The First Phase I/IIa Trial

Abstract: Purpose: Immunotherapy with Bacillus Calmette-Guerin (BCG) instillation is recommended for highrisk, non-muscle invasive bladder cancer. Bacillus Calmette-Guerin is not effective in advanced tumors, and better alternatives are warranted. Immunostimulating gene therapy with adenoviral vectors expressing CD40 ligand (AdCD40L) has shown efficacy in tumor models. CD40 ligand stimulates systemic immunity and may be effective in local and invasive human disease.Experimental Design: Patients with invasive bladder can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 24 publications
1
89
0
Order By: Relevance
“…Thus, both CD40L and IFN-b confer negative effects on carcinoma growth by improving tumor cell immunogenicity (4,14,15) and triggering direct antiproliferative and proapoptotic properties (37)(38)(39)(40)(41). Both CD40L and type I IFNs also act on immune cells to augment Th1 cell responses, enhance expression of MHC class I molecules, and generate NK and T cellmediated cytotoxicity (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both CD40L and IFN-b confer negative effects on carcinoma growth by improving tumor cell immunogenicity (4,14,15) and triggering direct antiproliferative and proapoptotic properties (37)(38)(39)(40)(41). Both CD40L and type I IFNs also act on immune cells to augment Th1 cell responses, enhance expression of MHC class I molecules, and generate NK and T cellmediated cytotoxicity (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…The CD40 pathway holds promise for the immunotherapy of various types of cancer, including non-Hodgkin's lymphoma (44), chronic lymphocytic leukemia (45), and carcinoma (46,47), and CD40 agonists have recently entered clinical trials, with promising results (38,48). The aforementioned role of RelA as a master regulator of IFN-b, coupled with its previously described involvement in the CD40-mediated Ag transporter and immunoproteasome gene expression (15), suggests that NF-kB may make a positive contribution to CD40L therapy by controlling antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that local adenoviral CD40L (AdCD40L) as well as CpG therapy can induce systemic antitumor responses in experimental bladder cancer (5,6). AdCD40L therapy has proven efficient and safe in both humans (7) and dogs (8). Consequently, we wanted to investigate whether local low-dose agonistic CD40 antibody injection could clear experimental bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56] In human bladder cancer patients, an adenovirus expressing CD40L induced large T-cell infiltrates in the bladder wall. 57 …”
Section: Conditioning Of Patients Receiving Car T-cell Therapymentioning
confidence: 99%